Methotrexate in combination with other DMARDs is not superior to methotrexate alone for remission induction with moderate-to-high-dose glucocorticoid bridging in early rheumatoid arthritis after 16 weeks of treatment: the CareRA trial. Issue 1 (30th October 2014) - Verschueren, P; De Cock, D; Corluy, L; Joos, R; Langenaken, C; Taelman, V; Raeman, F; Ravelingien, I; Vandevyvere, K; Lenaerts, J; Geens, E; Geusens, P; et al.
Abstract : Objectives: To compare the efficacy and safety of intensive combination strategies with glucocorticoids (GCs) in the first 16 weeks (W) of early rheumatoid arthritis (eRA) treatment, focusing on high-risk patients, in the Care in early RA trial. Methods: 400 disease-modifying antirheumatic drugs (DMARD)-naive patients with eRA were recruited and stratified into high risk or low risk according to classical prognostic markers. High-risk patients (n=290) were randomised to 1/3 treatment strategies: combination therapy for early rheumatoid arthritis (COBRA) Classic (methotrexate (MTX)+ sulfasalazine+60 mg prednisone tapered to 7.5 mg daily from W7), COBRA Slim (MTX+30 mg prednisone tapered to 5 mg from W6) and COBRA Avant-Garde (MTX+leflunomide+30 mg prednisone tapered to 5 mg from W6). Treatment modifications to target low-disease activity were mandatory from W8, if desirable and feasible according to the rheumatologist. The primary outcome was remission (28 joint disease activity score calculated with C-reactive protein <2.6) at W16 (intention-to-treat analysis). Secondary endpoints were good European League Against Rheumatism response, clinically meaningful health assessment questionnaire (HAQ) response and HAQ equal to zero. Adverse events (AEs) were registered. Results: Data from 98 Classic, 98 Slim and 94 Avant-Garde patients were analysed. At W16, remission was reached in 70.4% Classic, 73.6% Slim and 68.1% Avant-Garde patients (p=0.713). Likewise, no significant differences were shown in other secondary endpoints. However, therapy-related AEs were reported in 61.2% of Classic, in 46.9% of Slim and in 69.1% of Avant-Garde patients (p=0.006). Conclusions: For high-risk eRA, MTX associated with a moderate step-down dose of GCs was as effective in inducing remission at W16 as DMARD combination therapies with moderate or high step-down GC doses and it showed a more favourable short-term safety profile. EudraCT number: 2008-007225-39.